THE TRI-CENTRES OF FAMILY, SCHOOL AND COMMUNITY EDUCATION - Zeti Zeti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Secondary education is three educational centers consisting of family, school and community educational environments which progressively and integrally develop responsibility for the development of children's theories about learning. The family environment is the first environment and is considered the foundation of a child's education, which is also the beginning of further education and has a very important role in personality development. School education has a foundation, objectives, content, methods and other requirements which are arranged systematically in the form of a curriculum and are considered the basis of science. In social education, children apply several educational and teaching theories taught in previous educational institutions. Children apply and participate in the social environment. The organization of educational centers greatly influences the development of children's learning theories, which are carried out in an integrated manner and can make children become complete and responsible individuals. Children have professional skills which are the most important capital for entering society. Therefore, the triple education center is a series of integrated systems in the implementation of the educational process, which can lead students to maturity, which can be useful for the motherland and the nation. (N.M.S Agustin, 2018).